(3Sde Gdabg hGdOQGjI Ydi LeY GdfgGjI aj HOC GdNjQ hZGjIs - (3eMeO jMji Hf eMeO GdeNJGQ GdhdGJjs ((3ehQjJGfjG s)
(3ChdgG (B:s
(3CeG HYO adeG cGf Yde GdMOjK ef GTQa GdYdhe bOSkG hGaVdgG PNQkG GQGOJ TQM eNJUQ Gdabjg Gdhdi GdPi GNJUQg ef UMjM GdHNGQi GdeSei HLeY GdfgGjI ai HOC GdNjQ hZGjI hgh KdGKeGFI MOjK Shi NeSI hSejJg HSde Gdabg hGdOQGjI Ydi LeY GdfgGjI ai H s
(3BNQgG (B:s
(3hEfeG YedhG Ydi WdH QVi GdQMef hajg Odjd Ydi Cf QVi Cgd GdLfI cd efge HMGdg eY ENJdGa efGRdge hajg Odjd Ydi Cf GdQaY ai GdfYje hGdPi Ohfg jJSGhjGf YfO HSW LfGM GdQMeI hEXgGQ NdY GdbQH hGdCfHSGW jDNP Pdc ef bhdg JYGdi jG Cgd GdLfI YeheG GdQajY Gs
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eWGdYI heYfhfI HGdMHQ GdCShO hHgGeTgG JUhjHGJ s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
(3GdfSNI HgG JdhjK s
Keywords: (3GdMOjK h GdeUWdMs